"Solvent hydrogen‐bond occlusion": A new model of polar desolvation for biomolecular energetics. Issue 16 (20th March 2017) - Bazzoli, Andrea; Karanicolas, John
Abstract : Water engages in two important types of interactions near biomolecules: it forms ordered "cages" around exposed hydrophobic regions, and it participates in hydrogen bonds with surface polar groups. Both types of interaction are critical to biomolecular structure and function, but explicitly including an appropriate number of solvent molecules makes many applications computationally intractable. A number of implicit solvent models have been developed to address this problem, many of which treat these two solvation effects separately. Here, we describe a new model to capture polar solvation effects, called SHO ("solvent hydrogen‐bond occlusion"); our model aims to directly evaluate the energetic penalty associated with displacing discrete first‐shell water molecules near each solute polar group. We have incorporated SHO into the Rosetta energy function, and find that scoring protein structures with SHO provides superior performance in loop modeling, virtual screening, and protein structure prediction benchmarks. These improvements stem from the fact that SHO accurately identifies and penalizes polar groups that do not participate in hydrogen bonds, either with solvent or with other solute atoms ("unsatisfied" polar groups). We expect that in future, SHO will enable higher‐resolution predictions for a variety of molecular modeling applications. © 2017 Wiley Periodicals, Inc. Abstract : The "Solvent Hydrogen bond Occlusion" approach assigns desolvation free energies for individual polar groups, by evaluating the extent to which neighboring atoms prevent the polar group from engaging in hydrogen bonds with solvent. A single probe water molecule is considered, which can occupy grid points around the polar group of interest; the energetics on the grid reflect the preferred hydrogen bonding geometry for the polar atom of interest (color gradient). Neighboring atoms (shown in gray) sterically occlude the probe water from certain locations on the grid: by writing a partition function that sums over these grid points, we can explicitly evaluate the desolvation free energy due to these occluding atoms.